Implementasi Manajemen Sistem Pembelajaran pada Program Pengajaran Bahasa Arab Online Usia Dewasa - Farhan, Ahmad Riyadhi; Habib, Ahmad; Arba’ah, Ima Maulani; Subagyo, Ahmad; Adawiyah, Rabiatul (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Purpose - This study aims to describe the implementation of the learning management system, analyze the implementation of adult-based (andragogical) instructional activities, and identify the constraints and solutions in the online Arabic language learning program for adults at Maha Arabic Center. Design/Methodology/Approach - This qualitative study employed a single-case embedded case study design. Data were collected through semi-structured in-depth interviews with managers, instructors, and adult learners, as well as passive participant observation of 24 online learning sessions conducted via Zoom and document analysis. Findings - The findings indicate that: (1) the implementation of the learning management system involves the use of supporting digital tools such as Zoom, Canva, and Google Forms; (2) the instructional process is carried out through structured learning activities tailored to the self-directed learning characteristics of adult learners; and (3) the main challenges include participants’ limited availability and the absence of an integrated learning platform, which are addressed by providing recorded sessions and optimizing regular coordination. Research Limitation/Implications - This study is limited to a single non-formal educational institution and employs a case study approach; therefore, the findings cannot be generalized broadly. Nevertheless, the results offer practical implications for the development of andragogy-based online Arabic language learning management systems for adult learners.